La domus di Francesco Eustachi a Caselle Lomellina (1475-1487) - Zorzoli , Caterina (Opus Incertum, 2019)
The architectural complex of Cascina Caselle, now in the province of Pavia, stands in a territory for which the duke Galeazzo Maria Sforza always showed a certain predilection. The suburban villa built in the eighties of the 15th century at the behest of Francesco Eustachi (1415-1487), a clergyman hailing from Pavia who used his influence in the ducal court to obtain the title of apostolic protonotary, is small and annexed to the court of a farm. The analysis of archival sources has allowed to bring forth the phases of the building’s architectural path and to hypothesize that, at the death of the protonotary, the domus was equipped with updated architectural elements, such as the Roman-style cornices and the coffered rosettes, but also of elements characterized by a more lingering language, such as the gable of the entrance portal. The antiquarian taste of the client is also reflected in the fresco and graffiti decoration of the two ground floor rooms, most likely aimed at the celebration of illustrious men; regarding these works, the names of two masters involved in the construction of Pavia’s cathedral and charterhouse have also emerged: Ambrogio da Fossano, known as Bergognone, and Gabriele da Cassano.